Physiology and proteomics analyses reveal the regulatory mechanism of mepiquat chloride in soybean - Song, Shuang; Li, Xiaomei; Tian, Yumei; Zhou, Xinyu; Qu, Zhipeng; Liu, Jun; Dong, Shoukun (Frontiers in Sustainable Food Systems, 2023)
Soybean is an important grain and oil crop cultivated worldwide. Mepiquat chloride (DPC), a plant growth regulator, is widely used in cotton planting; however, its application in soybean remains rarely studied. Herein, we explored DPC regulation in soybeans using morphology, physiology, and proteomics analyses. Morphological and physiological analyses showed that DPC significantly reduced the plant height and shoot dry weight, promoted the growth of lateral roots in a specific concentration range, increased the activities of the leaf protective enzymes (superoxide dismutase and catalase), and decreased and increased malondialdehyde and total flavonoid contents, respectively. Proteomic analysis of leaves treated with 100 mg/L DPC revealed that multiple proteins related to plant growth and stress resistance were regulated after treatment. The key proteins involved in photosynthesis and cell wall elongation in the two varieties of soybean were significantly downregulated and those related to promoting lateral root growth and stress resistance were significantly upregulated. Overall, DPC inhibited shoot growth and photosynthesis in soybean but promoted lateral root growth, enhanced protective enzyme activity, and improved the ability of plants to resist abiotic stress. This study preliminarily determined the suitable DPC concentration for soybean spraying and provided a theoretical basis for its rational application.